A Logic Petri Net-Based Repair Method of Process Models with Incomplete Choice and Concurrent Structures - Teng, Yuanxiu; Qi, Liang; Du, Yuyue (Computing and Informatics, 2020)
Current model repair methods cannot repair incomplete choice and concurrent structures precisely and simply. This paper presents a repair method of process models with incomplete choice and concurrent structures via logic Petri nets. The relation sets are constructed based on process trees, including branch sets, choice activity sets and concurrent activity sets. The deviations are determined by analyzing the relation between relation sets and activities in the optimal alignment. The model repair method is proposed for models with incomplete choice and concurrent structures via logic Petri nets according to different deviation positions. Finally, the correctness and effectiveness of the logic Petri net-based repair method are illustrated by simulation experiments.